2022
DOI: 10.1002/hep4.1971
|View full text |Cite
|
Sign up to set email alerts
|

A new detection system for serum fragmented cytokeratin 18 as a biomarker reflecting histologic activities of human nonalcoholic steatohepatitis

Abstract: Caspase‐generated fragmented cytokeratin 18 (fCK18) is recognized as a useful noninvasive biomarker in the diagnosis of nonalcoholic fatty liver disease (NAFLD), particularly nonalcoholic steatohepatitis (NASH). However, fCK18 measurement is not applied clinically due to widely variable cut‐off values under the current enzyme‐linked immunosorbent assay platform. Therefore, we developed a highly sensitive chemiluminescent enzyme immunoassay using newly developed monoclonal antibodies against fCK18 and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…For the MTX and non-MTX group, there was a significant relationship between the level of ALT and CK-18 levels. Many previous studies have published similar findings (31)(32)(33). Altaf et al reported that ALT levels correlated with CK-18 in a study comprising 148 NAFLD subjects in Pakistan (33).…”
Section: Discussionsupporting
confidence: 53%
“…For the MTX and non-MTX group, there was a significant relationship between the level of ALT and CK-18 levels. Many previous studies have published similar findings (31)(32)(33). Altaf et al reported that ALT levels correlated with CK-18 in a study comprising 148 NAFLD subjects in Pakistan (33).…”
Section: Discussionsupporting
confidence: 53%
“…The search for alternative plasma biomarkers has increased due to the fact that serum ALT levels are not always predictive of MAFLD. Markers like caspase-generated fragmented cytokeratin 18 (fCK18), β-trophin, and adipokines like adiponectin and visfatin are currently being developed as alternatives to ALT and AST for the detection of MAFLD [35][36][37].…”
Section: Liver Disease Classificationmentioning
confidence: 99%
“…We conclude that these results do not suggest progressive liver injury over the course of the study. It should be noted that suggested thresholds vary quite markedly, 36 , 37 , 38 , 39 , 40 , 41 and in most studies and systematic reviews, researchers suggest that CK‐18 fragment results are viewed alongside a range of other measures (e.g. liver biopsy) to determine the degree of hepatocyte inflammation.…”
Section: Discussionmentioning
confidence: 99%